# Breuken haakjesregel (reeks 1)

#### Bereken

1. $$-\left(\frac{3}{-5}\right)-\left(\frac{6}{-5}\right)$$
2. $$+\left(\frac{-7}{4}\right)-\left(\frac{3}{-8}\right)$$
3. $$+\left(\frac{6}{-7}\right)+\left(\frac{2}{5}\right)$$
4. $$+\left(\frac{-14}{11}\right)-\left(\frac{-4}{-5}\right)$$
5. $$+\left(\frac{15}{-2}\right)+\left(\frac{7}{3}\right)$$
6. $$-\left(\frac{15}{8}\right)-\left(\frac{-6}{-5}\right)$$
7. $$+\left(\frac{14}{-15}\right)+\left(\frac{-4}{11}\right)$$
8. $$-\left(\frac{12}{5}\right)+\left(\frac{6}{5}\right)$$
9. $$+\left(\frac{10}{11}\right)+\left(\frac{12}{-5}\right)$$
10. $$+\left(\frac{-8}{3}\right)-\left(\frac{10}{-11}\right)$$
11. $$-\left(\frac{-8}{-11}\right)-\left(\frac{-2}{5}\right)$$
12. $$+\left(\frac{-10}{-13}\right)+\left(\frac{-4}{3}\right)$$

#### Bereken

##### Verbetersleutel

1. $$-\left(\frac{3}{-5}\right)-\left(\frac{6}{-5}\right)\\= \frac{3}{5}+\frac{6}{5}\\=\frac{3+6}{5}\\=\frac{9}{5}$$
2. $$+\left(\frac{-7}{4}\right)-\left(\frac{3}{-8}\right)\\= \frac{-7}{4}+\frac{3}{8}\\=\frac{-14}{8}+\frac{3}{8}\\=\frac{-14+3}{8}\\=\frac{-11}{8}$$
3. $$+\left(\frac{6}{-7}\right)+\left(\frac{2}{5}\right)\\= \frac{-6}{7}+\frac{2}{5}\\=\frac{-30}{35}+\frac{14}{35}\\=\frac{-30+14}{35}\\=\frac{-16}{35}$$
4. $$+\left(\frac{-14}{11}\right)-\left(\frac{-4}{-5}\right)\\= \frac{-14}{11}-\frac{4}{5}\\=\frac{-70}{55}-\frac{44}{55}\\=\frac{-70-44}{55}\\=\frac{-114}{55}$$
5. $$+\left(\frac{15}{-2}\right)+\left(\frac{7}{3}\right)\\= \frac{-15}{2}+\frac{7}{3}\\=\frac{-45}{6}+\frac{14}{6}\\=\frac{-45+14}{6}\\=\frac{-31}{6}$$
6. $$-\left(\frac{15}{8}\right)-\left(\frac{-6}{-5}\right)\\= \frac{-15}{8}-\frac{6}{5}\\=\frac{-75}{40}-\frac{48}{40}\\=\frac{-75-48}{40}\\=\frac{-123}{40}$$
7. $$+\left(\frac{14}{-15}\right)+\left(\frac{-4}{11}\right)\\= \frac{-14}{15}-\frac{4}{11}\\=\frac{-154}{165}-\frac{60}{165}\\=\frac{-154-60}{165}\\=\frac{-214}{165}$$
8. $$-\left(\frac{12}{5}\right)+\left(\frac{6}{5}\right)\\= \frac{-12}{5}+\frac{6}{5}\\=\frac{-12+6}{5}\\=\frac{-6}{5}$$
9. $$+\left(\frac{10}{11}\right)+\left(\frac{12}{-5}\right)\\= \frac{10}{11}-\frac{12}{5}\\=\frac{50}{55}-\frac{132}{55}\\=\frac{50-132}{55}\\=\frac{-82}{55}$$
10. $$+\left(\frac{-8}{3}\right)-\left(\frac{10}{-11}\right)\\= \frac{-8}{3}+\frac{10}{11}\\=\frac{-88}{33}+\frac{30}{33}\\=\frac{-88+30}{33}\\=\frac{-58}{33}$$
11. $$-\left(\frac{-8}{-11}\right)-\left(\frac{-2}{5}\right)\\= \frac{-8}{11}+\frac{2}{5}\\=\frac{-40}{55}+\frac{22}{55}\\=\frac{-40+22}{55}\\=\frac{-18}{55}$$
12. $$+\left(\frac{-10}{-13}\right)+\left(\frac{-4}{3}\right)\\= \frac{10}{13}-\frac{4}{3}\\=\frac{30}{39}-\frac{52}{39}\\=\frac{30-52}{39}\\=\frac{-22}{39}$$
Oefeningengenerator vanhoeckes.be/wiskunde 2022-05-24 05:39:37